1982
DOI: 10.1136/hrt.47.1.90
|View full text |Cite
|
Sign up to set email alerts
|

Pyrophosphate heart scan in patients with progressive systemic sclerosis.

Abstract: SUMMARY Scintigraphic examination of the myocardium, using 1Tc-labelled pyrophosphate, was carried out in 17 patients suffering from systemic sclerosis. This connective tissue disorder very often affects the myocardium secondarily. The results of the cardiac scan were compared with the information obtained from the electrocardiogram of systolic time intervals. In addition, spirometry was undertaken to detect a potential relation between cardiac and pulmonary involvement. The scan was found to be positive in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

1983
1983
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 8 publications
(3 reference statements)
0
4
0
1
Order By: Relevance
“…Recently it has been shown that thallium-201 scintigrams and pyrophosphate scans can detect perfusion defects or cell necrosis in the myocardium in patients with systemic sclerosis (Alexander et al, 1981;Duska et al, 1982). Follansbee et al (1984) studied 23 patients (6, 23%, had clinical evidences of cardiac involvement) and found that 20 patients (77%) had abnormal thallium redistribution scan.…”
Section: Discussionmentioning
confidence: 99%
“…Recently it has been shown that thallium-201 scintigrams and pyrophosphate scans can detect perfusion defects or cell necrosis in the myocardium in patients with systemic sclerosis (Alexander et al, 1981;Duska et al, 1982). Follansbee et al (1984) studied 23 patients (6, 23%, had clinical evidences of cardiac involvement) and found that 20 patients (77%) had abnormal thallium redistribution scan.…”
Section: Discussionmentioning
confidence: 99%
“…lished (6). In the present paper we report the findings in systemic lupus erythematosus, polymyositis and spondylitis ankylopoetica.…”
Section: /28mentioning
confidence: 72%
“…Pyrophosphate does not accumulate into lesions of earlier date (7). Our team was the first to use scintigraphic detection of a cardiac involvement in systemic connective tissue disease (6). The ECG, on the other hand, detects only such a type of heart damage which manifests itself with a disorder in the electrophysiology of the organ.…”
Section: Discussionmentioning
confidence: 99%
“…Positive findings have also been reported in some cases of angina pectoris (9), of myocarditis (11) and pericarditis (13), following an impairment of the myocardium with doxorubicine (6), after defibrillation (2), in cases of heart aneurysma (12) or heart contusion (19) as well as after impairment of the myocardium caused by radiation (17). In addition, a few authors have reported positive scintigraphic findings in cardiomyopathies of different etiology (4,20). In our opinion, the pyrophosphate scintigram is of considerable value in the diagnosis of cardiomyopathies which is difficult when using routine examination methods only (5).…”
Section: Introductionmentioning
confidence: 96%